1988
DOI: 10.6028/nbs.ir.87-3670
|View full text |Cite
|
Sign up to set email alerts
|

A review of autoclaved aerated concrete products

Abstract: This report is a review of the properties and performance of autoclaved aerated concrete. The material has a relatively low thermal conductivity combined with loadbearing capacity for use in structural and non-structural applications. This feature may make its use attractive for energy-conserving applications. For this reason, the review was conducted at the request of the U.S. Department of Energy.The review addressed an overview of the manufacturing process, uses of autoclaved aerated concrete in building co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…According to Mathey and Walter J. Jr. Rossiter (1988), water absorption for the autoclaved concrete is neglected because it is considered low, but the results found in this assay indicated that the amount of water absorbed was high.…”
Section: Water Absorptionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Mathey and Walter J. Jr. Rossiter (1988), water absorption for the autoclaved concrete is neglected because it is considered low, but the results found in this assay indicated that the amount of water absorbed was high.…”
Section: Water Absorptionmentioning
confidence: 93%
“…In Brazil, NBR 13438 (ABNT, 2013a) defines autoclaved aerated concrete blocks (AACB) as lightweight concrete which is prepared by adding aluminum powder and then the mixture undergoes a steam-saturated curing process under controlled pressure (12 atm) at a temperature of between 180°C and 200°C. According to Mathey e Walter J. Jr. Rossiter (1988), this curing process allows the material to have resistance strengths above 1.5 MPa and densities of around 500 kg/m 3 , and this also results in well-distributed spherical pores with low capillarity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the severe adverse effects of shrinkage in the concrete, researchers suggested that lightweight aerated concrete in non-load bearing elements should not be subjected to temperature above 700 C since major cracks and collapse can occur above that temperature. 8,[13][14][15][16] Over the years, the behaviour of composite sandwich panels and their performances during exposure to elevated temperatures and fire events were investigated. Vilches et al 12 evaluated the performance of ultra-lightweight foam concrete with varying densities of 150 to 500 kg/m 3 , enduring elevated temperature from 1 hour to more than 3 hours depending on the cement percentage and density.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, concrete could be prone to shrinkage phenomenon when it was subjected to dry conditions such as high temperature or fire events. Due to the severe adverse effects of shrinkage in the concrete, researchers suggested that lightweight aerated concrete in non‐load bearing elements should not be subjected to temperature above 700°C since major cracks and collapse can occur above that temperature 8,13‐16 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, they require to be used in combination with load-carrying elements like solid bricks or concrete slabs. Porous building blocks, on the other hand, aim to combine both load-carrying and thermal insulation capacities [1][2][3]. Well-known commercial variants are cellular glass or cellular concrete.…”
Section: Introductionmentioning
confidence: 99%